Effectiveness of Job Aids and Post Performance Review on Staff Implementation of Discrete Trial Instruction. Issue 2 (3rd April 2017) - Parnell, Ashley M.; Lorah, Elizabeth R.; Karnes, Alison; Schaefer-Whitby, Peggy
ABSTRACT: Discrete-trial instruction (DTI) is a well-established instructional method for teaching children with autism. Accurate implementation of DTI procedures requires that staff be well trained. This study examined the effectiveness of job aids followed by post performance review of strengths, errors, and accuracy on discrete trial instructional accuracy in three participants who conducted DTI within their current job positions. Additionally, primary training procedures were embedded within a meta-shaping procedure, which involved the gradual and systematic introduction of three levels of behavioral components required for accurate implementation of the DTI sequence with mastery criteria set at 90% accuracy across all three levels. As demonstrated in a changing criterion within a multiple baseline design, staff demonstrated increases in DTI accuracy following the initiation of the job aid condition; however, some degree of performance-based feedback was required to establish high levels of procedural fidelity across the DTI sequence. Performance accuracy on maintenance probes remained at high levels. These findings provide support that job aids followed by performance-based feedback may be an effective and efficient method for shaping high levels of DTI procedural fidelity in staff. Additionally, gradual shaping of the DTI accuracy may scaffold performance, minimize errors, and increase social validity.